Results based personnel performance system a key tool in performance management and effective service delivery by Zimbabwean local authorities. The case of Chipinge town council. - Mufukare, Nyasha K. (Midlands State University, 2017)
Zimbabwean Local Authorities have faced immense challenges in service provision during the past years due to economic challenges but however a poor performance management culture or system has been attributed to this drastic failure to provide services effectively and efficiently. The research analyses the adoption and implementation of Results Based Personnel Performance Management System and its impact on the provision of services with a special focus on Chipinge Town Council. The ZIMASSET economic blueprint of 2013 came in as a vibrant policy guiding results attainment in the public sector and saw the signing of performance agreement contracts for senior officials such as Town Clerks/Town Secretaries. The research aims at investigating the awareness of council officials and councilors to the adoption of this system so that it will be established whether the Local Authority is able to achieve the intended goals and missions. The mechanisms in place for the successful implementation of the system will also be analyzed and how they impact on higher performance that will culminate in an efficient and effective service delivery system by the Local Authority. The various challenges that hinder effective implementation were also highlighted. The impact of RBPPS on service delivery was highlighted. Various literature on RBPPS was explored and it was linked to the adoption of RBPPS at CTC and how it improves service delivery. The researcher used both qualitative and quantitative research designs to present the findings that were gathered through the research instruments which were interviews and questionnaires. The findings indicated that CTC has greatly improved on its service delivery system by prioritizing service delivery through procurement of graders, refuse truck and completing water works at Bangaazan treatment plant. This was due to the fact that the Local Authority was given targets and therefore they are committed to achieve these performance targets so that the Town Secretaries performance contract will be renewed. The research recommends strong human resources policies that are aimed at achieving a higher caliber of performing employees or staff and also engage on capacity building programmes that will help the employees to adapt to this new performance management culture so that service can be improved in the Town.